Estudo de eficiência energética no acionamento de um compressor parafuso em um sistema de ar comprimido - Aguiar, Victor de Paula Brandão (2008)
This work presents a study of energy efficiency on a compressed air system with screw compressor showing energy consumption according to the used drive. Screw compressors represents today about 50% of all produced compressors. They are applied in beverages industries, pharmaceutical industries, chemical industries and textile industries too. Three drives types are studied: two classics and the variable speed drive (VSD). The classic drives are on/off cycle and dual cycle. Using induction motor abc model was conducted the iterative method for the measurement of mechanical torque equivalent to the work’s pressure. From this, the simulations were performed with all drives. The study also shows the influence of work’s pressure on the system energy balance, on the drives, as well as the admission’s temperature influence in the energy conservation process. The screw compressor presents reduced energy consumption in the use of VSD compared with dual cycle. The work also presents a reduction in the compressor energy consumption based in the reduction of work’s pressure.